Anticardiolipin antibodies from syphilis and systemic lupus erythematosus induce leakage in cardiolipin vesicles - Cremião, M. P.D.; Ceili, C. M.; Chaimovich, H. (My University, 1996)
Anticardiolipin antibodies from sera of patients with systemic lupus erythematosus or syphilis induced leakage of entrapped carboxyfluorescein (CF) from cardiolipin (CL)/phosphatidylcholine(PC) vesicles prepared by sonication of equimolar mixtures of CL:PC. The sera dilution used here was 1:7500. IgG (5-20 μg/ml) from the same sera, not containing B2GPI, also produced a concentration-dependent leak. Vesicle leakage was inhibited by salt and was not detected with vesicles prepared exclusively with phosphatidylcholine. The demonstration of antibody-induced vesicle leakage offers a convenient system to investigate the mechanism of antibody-lipid binding as well as a potential diagnostic tool.
Keywords: Anticardiolipin antibodies; Carboxyfluorescein; Cardiolipin; Syphilis; Systemic lupus erythematosus; Vesicles